El programa el edelim como estrategia didáctica, para potenciar el aprendizaje de la corriente eléctrica en los estudiantes del segundo año de bachillerato general unificado de la unidad educativa intercultural bilingüe Mushuk Rimak de la parroquia San Lucas. Periodo 2015-2016 - Gualán Macas, Edwin Patricio (2016)
The research work Edilim called the program as a teaching strategy to enhance learning of electric current in the sophomores Unified School General Intercultural Bilingual Education Unit Mushuk Rimak Parish San Lucas. 2015-2016 period, aims to help improve the quality of education, for which the target is raised: apply the program to enhance learning edilim electric current. The research responded to a descriptive design phases that were used in their order were: Comprehensive, was to analyze, synthesize and evaluate learning difficulties of electric current to be improved with Edilim program is the diagnosis learning difficulties of electric current through an exploratory survey, Edilim program was implemented as a model to guide the learning of electric current, plus workshops were developed to enhance the learning of electrical current, the program's effectiveness was assessed the Edilim as a teaching strategy by Wilcoxon rank test to enhance learning of electric current. Finally analyzing the main results, it is determined that: most of the students has difficulty in the learning of the electric current, their elements, law of Ohm, electric circuits in series, parallel, mixed and measure instruments, likewise, the educational ones use traditional didactic resources, leaving aside as videos, multimedia and programs. All these difficulties, or cognitive deficits present in the learning needs of electric current can be reduced with the implementation of the program Edilim as a teaching strategy in enhancing knowledge